CHANGES, TRENDS AND RELATIONSHIPS BETWEEN AVERAGE INCOME AND CONSUMPTION EXPENDITURES PER HOUSEHOLD IN ROMANIA IN THE PERIOD 2007-2017 - Agatha POPESCU; Toma Adrian DINU; Elena STOIAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the dynamics of average monthly income (AMI) and average monthly expenditure (AME) per household and the relationships between these indicators of living standard in Romania in the period 2007-2017. The dynamic analysis, descriptive statistics, correlations, and regression functions were used to process data. The results pointed out that both AMI and AME per household increased in Romania, but income growth rate was higher than expenditure increase rate. In the rural area, AMI per household is 64.3 % of the urban average and 76.1 % of the national one. AME is the highest in the urban area. In the rural households it represents 77.1 % of the urban one and 85.6 % of the national average. A person living in the rural area spends three times less money than an urban citizen. The share of AME in the AMI decreased from 80.7 % in 2007 to 66.5% in 2017, because the income growth rate was higher than the spending rate. In the rural communities, this percentage was 74.9 in 2017, higher than in the urban area. The expenditures on food and non alcoholic beverages also increased, being higher in the urban area. The share of food and non alcoholic beverages in AME is 29 % in the rural area, the highest in the country. AME per household accounts for 61.1 % of GDP, placing Romania on the 8th position in the EU-28. Also, Romania comes on the top position for 17 % share of expenditure on food and non-alcoholic beverages in GDP. The correlations proved a high and positive connection between income and expenditure. According to the regression equations, an AMI increase by Lei 100 will increase AME by Lei 52.9 at the national level, by Lei 49.30 in the urban household, by Lei 58.96 in the rural household, will raise consumption expenditure on food and non alcoholic beverages by Lei 12.02 nationally, by Lei 10.39 in the urban household and by Lei 14.58 in the rural one. Household income is still lower in Romania compared to other EU countries. A new strategy is required to increase population's income in order to improve life quality and reduce the discrepancies with the other EU countries.